ANALISIS DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA LABORATORIUM PARAHITA DIAGNOSTIC CENTER CABANG JEMBER - Suharto, Akhmad (Universitas Jember, 2014)
The problem in this study was motivated by complaints from customers for services received by the customer, which should not happen considering the complaint that the motto of Parahita lab is to provide services with a vengeance. While competition in the field of health services increasingly stringent, making it mandatory for Parahita Laboratory to continue to improve services. Because if standing companies offering the same services, customers still rely on the Health Parahita Laboratory Diagnostic Center Jember Branch. The problem in this research is to measure how much the level of customer satisfaction of each variable intangibles / tangibles, reliability, responsiveness, empathy and assurance. And to determine which variables are the dominant influence on customer satisfaction Parahita Laboratory Diagnostic Center Jember Branch. Population of this study is that all customers who check in Parahita Laboratory Diagnostic Center Branch in Jember for 1 month starting on 20 December 2012 until 20 January 2013. The samples in this study with purposive sampling with criteria (1) The customer has to check the DC Parahita Laboratory Jember branch over 2kali. (2) Customers who can provide information or be able to communicate. The results of this study are known (1) that the calculated F is greater than F table (22.552> 2.3861) so it can be concluded simultaneously all independent variables affect the dependent variable. (2) that t variable intangibles (2,122), reliability (2.271), responsiveness (2,186), empathy (7.648), collateral (2,794), greater than t table (2.0211) that proved to significantly affect customer satisfaction . (3) variable empathy dominant influence on customer satisfaction.